Design and optimization of three-resonator locally resonant metamaterial for impact force mitigation. (6th August 2018) - Li, Q Q; He, Z C; Li, Eric; Cheng, A G
Abstract: In this paper, we propose a three-resonator metamaterial (TRM) to enhance the attenuation effect of impact stress waves. Based on the theoretical analysis, the width of the negative effective mass frequency regions of TRM is wider than that of single-resonator metamaterial (SRM) and dual-resonator metamaterial (DRM). In numerical cases, the superior performance of TRM is validated based on the impact wave model and the multi-corner thin-walled column crash model compared with SRM and DRM. It is found that the high attenuation effects of frequency spectrum and impact force can be achieved with TRM. In addition, the multi-objective optimization analyses of TRM are also conducted to minimize the metamaterial mass, body acceleration and impact force in two practical examples including the structural crashworthiness of the thin-walled column model and the trolley model.